PERUBAHAN KARAKTERISTIK FISIKOKIMIA MINYAK SELAMA PENGGORENGAN DENGAN METODE DEEP FAT FRYING: KAJIAN LITERATUR - Moh Taufik; Yoni Atma (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Deep fat frying is a popular frying method in the world. There are several chemical reactions that occur during the frying process, namely oxidation, hydrolysis and polymerization. These reactions will influence to the physicochemical properties of the oil, such as increasing-decreasing in the peroxide value, an increasing in free fatty acids, a decreasing in the iodine value, an increasing in viscosity and a decrease in the smoke point. The types of oil will affect to the stability of physicochemical properties. Oils rich in unsaturated fatty acids tend to have low heating stability. The type of fried food will also affect the stability of the oil used. Animal-based food (chicken, chicken nuggets and cod) tend to cause oil deterioration more quickly than plant-based foods (potato and banana).